Philosophy in a Meaningless Life A System of Nihilism, Consciousness and Reality - Tartaglia, James (Bloomsbury Academic, 2016)
Provides an account of the nature of philosophy which is rooted in the question of the meaning of life. It makes a powerful and vivid case for believing that this question is neither obscure nor obsolete, but reflects a quintessentially human concern to which other traditional philosophical problems can be readily related; allowing them to be reconnected with natural interest, and providing a diagnosis of the typical lines of opposition across philosophy's debates. James Tartaglia looks at the various ways philosophers have tried to avoid the conclusion that life is meaningless, and in the process have distanced philosophy from the concept of transcendence.